(untitled) (Third Sector Social Economic Review, 2020)
Scandals experienced in the field of accounting and financial reporting revealed the importance of auditing. In this sense, scientific studies and the focus on this subject have increased rapidly over the years. National and international auditing regulations have been rapidly renewed with the experience of financial reporting scandals, and academic research has gained more importance for developments in this area. This paper aims to evaluate the scientific articles in the field with a general perspective and examine the studies published in the field with content analysis. In the study, one of the data collection methods used in qualitative research, examining written documents, is used. In order to determine the articles to be examined, some scanning and selection parameters have been set. Based on the keyword ""auditing"", articles published in Turkey between 2002-2019 are scanned in ULAKBIM TR Index. Types and number of publications by years, the journals published, the authors’ distribution by numbers, and institutions they work for, and distribution by research subjects of 115 scientific articles published in the auditing field between the selected years are examined.